Poverty and place in North America: Overview - Mary Jo Bane; Rene Zenteno (Luxembourg Income Study (LIS), 2005)
This paper provides an overview of poverty in North America. In it we look at the three countries of North America, Mexico, the US, and to a lesser extent Canada and attempt to both describe poverty as it exists in the three countries and explore some of the correlates of poverty. In doing so, we attempt to bring together the concepts and approaches used mostly in studying poverty in developing countries and those used in developed countries. We propose some definitions of poverty that we believe can be usefully applied across very different countries. We explore some correlates of poverty in the three countries, and both the similarities and the differences in the correlates of poverty across the three. We take note of the policy issues that are raised by these relationships. As might be expected, we raise more questions that we answer, about both our approach and our findings. We begin with an overview of growth and inequality in the three countries. The second section of the paper presents concepts and measures of poverty and reports the overall incidence of poverty in the three countries using various measures. The third section explores the relationship between the level of economic development and poverty, both between and within countries. The fourth section looks at the relationships between household composition and poverty and between race/ethnicity and poverty in the US and Mexico. The final section briefly raises policy issues that emerge from the analysis.
Keywords: 330; Armut; Wirtschaftswachstum; Einkommensverteilung; Rasse; Ethnische Gruppe; Mexiko; USA; Kanada